1976
DOI: 10.1099/00221287-93-2-309
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Metabolism in Agaricus bisporus (Lange) Sing.: Changes in Soluble Carbohydrates during Growth of Mycelium and Sporophore

Abstract: Changes in the ethanol-soluble carbohydrate content of Agaricus bisporus mycelium and sporophores grown on semi-defined media and commercial compost were studied. The accumulation of mannitol in the sporophore during its growth was not accompanied by an increase in mycelial mannitol. The other major soluble carbohydrate of the sporophore, trehalose, decreased throughout the growth of the sporophore; a parallel decrease was observed in the mycelium. The main accumulation of mannitol was in the pileus and stipe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0
1

Year Published

1977
1977
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(128 citation statements)
references
References 8 publications
8
119
0
1
Order By: Relevance
“…bisporus As A. bisporus does not fruit in axenic culture, studies were undertaken using stage 1 (pin) sporophores as defined by Hammond & Nichols (1976). In stage 1 sporophores, metabolic effects owing to fiushing are not obscured by those arising from growth and maturation of sporophores which occur at later stages.…”
Section: Culture Of Organism and Sources Of Chemicals And Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…bisporus As A. bisporus does not fruit in axenic culture, studies were undertaken using stage 1 (pin) sporophores as defined by Hammond & Nichols (1976). In stage 1 sporophores, metabolic effects owing to fiushing are not obscured by those arising from growth and maturation of sporophores which occur at later stages.…”
Section: Culture Of Organism and Sources Of Chemicals And Enzymesmentioning
confidence: 99%
“…occurs periodically in a series of flushes approximately at weekly intervals; very few fruit bodies are produced between flushes. Hammond & Nichols (1976) first observed that, during fruit-body growth, concentrations of trehalose (percentage dry weight) declined in both sporophore and mycelium. Concentrations of protein in the sporophore also declined with growth.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it may increase the content of mannitol in natural C. sinensis (Wang et al 2009; Guan et al 2010). Increased mannitol is related to fruiting body initiation and development of A. bisporus (Kulkarni, 1990), and the mannitol content in the fruiting body of A. bisporus is about 8–20 times higher than that in mycelia (Hammond and Nichols 1976; Wannet et al 2000). …”
Section: Proteins Involved In Carbohydrate Metabolismmentioning
confidence: 99%
“…Mushrooms were harvested daily at their optimal commercial development stage corresponding to morphogenetic stages 2, 3 and 4, according to the classification of Hammond and Nichols (1976).…”
Section: Harvesting Production and Commercial Quality Parametersmentioning
confidence: 99%